Lineamenti di diplomatica generale - Nicolaj, Giovanna (Scrineum, 2013)
What is ’Diplomatics’ and what is its purpose? What are written records, and what are they for? The A. answers to these questions in this preparatory study of her recent handbook Lezioni di diplomatica generale (Roma 2007), suggesting a methodological reflection on ’Diplomatics’ beginning from the definition of document and investigating its typical forms (whitin its own historical system of documents) and its several functions.